A review upon medicinal perspective and designing rationale of DPP-4 inhibitors. (15th September 2021) - Kumar, Shubham; Mittal, Anu; Mittal, Amit
Graphical abstract: Highlights: Rationale and approaches involved in the development of DPP-4 inhibitors have been discussed in this manuscript. Clinical data of various DPP-4 inhibitors are included in this manuscript. Newer finding related to DPP-4 inhibitors have been discussed. Structure activity relationship (SAR), molecular docking is also included. This manuscript provides detailed insight of current and future prospective in the area of DPP-4 inhibitors research. Abstract: Type 2 Diabetes Mellitus (T2DM) is one of the highly prevalence disorder and increasing day by day worldwidely. T2DM is a metabolic disorder, which is characterized by deficiency in insulin or resistance to insulin and thus increases the glucose levels in the blood. Various approaches are there to treat diabetes but still there is no cure for this disease. DPP-4 inhibitor is a privileged target in the field of drug discovery and provides various opportunities in exploring this target for development of molecules as antidiabetic agents. DPP-4 acts by inhibiting the incretin action and thus decreases the level of blood glucose by imparting minimal side effects. Sitagliptin, vildagliptin, linagliptin etc. are the different DPP-4 based drugs approved throughout the world for the treatment of diabetes mellitus. Cyanopyrrolidines, triazolopiperazine amide, pyrrolidines are basic core nucleus present in various DPP-4 inhibitors and has potential effects. In the past few years, researchers had applied various approaches to synthesize potent DPP-4 inhibitors as antidiabetic agent without side effects like weight gain, cardiovascular risks, retinopathy etc. This review will also emphasize the recent strategies and rationale utilized by researchers for the development of DPP-4 inhibitors. This review also reveals about the various other approaches like molecular modelling, ligand based drug designing, high throughput screening etc. are used by the various research group for the development of potential DPP-4 inhibitors.